2007
DOI: 10.2460/ajvr.68.5.501
|View full text |Cite
|
Sign up to set email alerts
|

Changes in antimicrobial susceptibility in a population of Escherichia coli isolated from feedlot cattle administered ceftiofur crystalline-free acid

Abstract: Administration of CCFA provided selection pressure that favored transient expansion of multiple-resistant variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
85
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 20 publications
13
85
3
Order By: Relevance
“…5). Longitudinal studies have shown a transient increase of ceftiofur-resistant enteric bacteria during treatment (Lowrance et al, 2007). The pharmacokinetic and pharmacodynamic parameters influenced the selection of antimicrobial resistance during treatment, but fitness cost highly determined the persistence of the resistant bacteria after the end of treatment.…”
Section: Transmission Modelingmentioning
confidence: 99%
“…5). Longitudinal studies have shown a transient increase of ceftiofur-resistant enteric bacteria during treatment (Lowrance et al, 2007). The pharmacokinetic and pharmacodynamic parameters influenced the selection of antimicrobial resistance during treatment, but fitness cost highly determined the persistence of the resistant bacteria after the end of treatment.…”
Section: Transmission Modelingmentioning
confidence: 99%
“…Experimentally administration of ceftiofur to feedlot cattle was also associated with an increase in the population of ceftiofur-resistant isolates (Lowrance et al, 2007). It has been argued that active concentrations of ceftiofur and cefquinome in the intestines of treated animals are very low, as they are mainly excreted in urine with a limited portion, excreted in faeces (Hornish and Kotarski, 2002); see also MRL summary reports available at www.ema.europa.eu).…”
Section: Impact Of Cephalosporin Use On Selection and Amplification Omentioning
confidence: 99%
“…Calves administered intramuscular (IM) ceftiofur hydrochloride had a significantly increased number of ceftriaxoneresistant fecal bacteria following treatment (Jiang et al, 2006). Cattle administered ceftiofur crystalline-free acid had a 2-week increase in multidrug-resistant (ceftiofur, ampicillin, chloramphenicol, tetracycline, and sulfisoxazole) Escherichia coli (Lowrance et al, 2007).…”
Section: Chapter 1 -Introduction Literature Reviewmentioning
confidence: 99%